Direct and Indirect Speech Acts in the Drama “A Streetcar named Desire” written by Tennessee William - Mahdi Ahmad; Z Zainurrahman (Jurnal Langua, 2021)
A drama is a work filled with figurative languages ​​that are full of implied meanings. The purpose of writing a drama, of course, is to entertain the reader. However, a drama text can also be a source of pragmatic learning that is rich in expression. This research is one of pragmatic research on drama texts. Using content analysis techniques, the researchers attempted to portray the use of speech acts, both direct and indirect, used by Tennessee William in her play "A Streetcar named Desire". There are at least ten data collected by the researchers and interpreted briefly based on the rules of speech acts in the pragmatic concept. The conclusion drawn from the interpretation of the data is that there are various uses of indirect speech acts in the drama and also changes in the types of speech acts that show how dynamic the language used in the drama is.